# ln(lnx)=0?

*print*Print*list*Cite

### 1 Answer

Solve ln(ln(x))=0:

Use the fact that ln(x) and e^x are inverse functions: in particular, e^(ln(u))=u.

ln(ln(x))=0 Raise both sides with base e:

e^(ln(ln(x)))=e^0 a^0=1 for all a not zero, so:

ln(x)=1 Raise both sides with base e:

e^(ln(x))=e^1

x=e

---------------------------------------------------------------------------------

The solution is e where e is approximately 2.7182818284590; e is the base of the natural logarithm.

---------------------------------------------------------------------------------

Check: ln(ln(e))=ln(1)=0.

The graph of ln(ln(x)):

Note that the zero is at approximately 2.7 as expected.

**Sources:**